Determination of chlorpromazine and its metabolites in animal-derived foods using QuEChERS-based extraction, EMR-Lipid cleanup, and UHPLC-Q-Orbitrap MS analysis. (1st March 2023) - Dai, Jinxia; Lin, Hui; Pan, Yuning; Sun, Yanmin; Wang, Ye; Qiao, Jun-qin; Lian, Hong-zhen; Xu, Chun-xiang
Highlights: A method to determine CPZ and its metabolites in animal-derived foods was proposed. CPZ was prone to undergo hydrolytic transformation at high temperature. The structures of hydrolysates of CPZ were clarified based on HRMS and software. The method was suitably applied to analyze and screen CPZ-related risk compounds. Abstract: Chlorpromazine (CPZ) is abused in animal husbandry and can be extensively metabolized in humans and animals. However, the actual monitoring mainly focuses on the parent compound but lacks attention to its metabolites. A method was developed and validated firstly for identification and determination of CPZ and its four major metabolites in animal-derived foods using ultrahigh-performance liquid chromatography coupled with quadrupole-Orbitrap mass spectrometry in combination with QuEChERS preparation method. Satisfactory recoveries of analytes spiked in fish and pork samples ranged from 72 to 117 %, and limits of quantification were 2.0 and 1.0 μg kg −1 for fish and pork samples respectively. Moreover, through the hydrolysis experiments of CPZ, its hydrolysates, such as CPZ-sulfoxide, CPZ- N -oxide and CPZ-sulfoxide- N -oxide, were identified as potential risk compounds. The developed method has been successfully applied to the determination of CPZ and its metabolites in actual commercial samples, as well as to the screening of other CPZ-related risk compounds.